Analisis Faktor – Faktor Yang Mempengaruhi Kebijakan Dividen - Feisy Christina Puteri; Ari Budi Kristanto; Paskah Ika Nugroho (Conference In Business, Accounting, And Management (CBAM), 2012)
This research used multiple regression method to examine the relationships between the profitability, investment opportunity, leverage and dividend payout ratio previous year with dividend policy. Sampling method used in this research are purposive sampling method. Hypotheses tests of this research used 65 sample of manufacturing company which were listed in the Indonesian Stock Exchange ( IDX ) from the year of 2007 until 2010. Results of this research show that the dividend payout ratio previous year had a significant positive effects on the dividend policy, while profitability, leverage and investment opportunity had no significant effects on the dividend policy.Key words : profitability, investment opportunity, leverage, dividend payout ratio previous year and dividend policy